Implementation of corporate governance mechanisms in tourism - Jabbarov, Fuad (Annals of Spiru Haret University. Economic Series, 2018)
The article is devoted to forming of effective mechanisms that regulate economic activity of subjects. The economic state affects activity of companies, especially in tourism. The aim of this paper is to show that how implementation of corporate governance mechanisms provides greater transparency in the tourism sector, as well as a higher level of alignment of the domestic regulatory framework with the principles applied in the developed economies in this industry. Different internal and external factors affecting the steady development and development of companies. Currency parity and increase of bank interest rates and their influence on a tourist stream. Forming of steady mechanisms by means of implementation of elements and principles of corporate management. Possibilities of adaptation and implementation of mechanisms of corporate management.